Common mental disorders and intimate partner violence against pregnant women living with HIV in Cameroon: a cross-sectional analysis - Angela M. Parcesepe; Evette Cordoba; John A. Gallis; Jennifer Headley; Berenger Tchatchou; John Hembling; Claudian Soffo; Joy Noel Baumgartner (BMC, 2021)
Abstract Background Women living with HIV are at increased risk of poor mental health and intimate partner violence (IPV). Mental health disorders have been consistently associated with suboptimal HIV-related outcomes. Little is known about the prevalence or correlates of mental health disorders among pregnant women living with HIV in sub-Saharan Africa. Methods This study assessed the prevalence of probable common mental disorders (CMD), i.e., depressive or anxiety disorders, and the relationship between probable CMD and recent IPV among pregnant women living with HIV in Cameroon. The sample included 230 pregnant women living with HIV aged > 18 enrolled in care at 10 HIV clinics in Cameroon. Probable CMD was assessed with the WHO Self Reporting Questionnaire (SRQ-20). Multivariable logistic regression was conducted to assess the relationship between IPV and probable CMD. Results Almost half (42%) of participants had probable CMD using a 7/8 cut-off of the SRQ-20. Emotional, physical, and sexual IPV were reported by 44, 37, and 31% of respondents, respectively. In multivariable regression analyses, all forms of IPV assessed were significantly associated with greater odds of probable CMD. Conclusions Pregnant women living with HIV in Cameroon had a high prevalence of probable CMD and IPV. Screening and services to address IPV and mental health are urgently needed for this population. Integrated interventions to both prevent and screen and address IPV and probable CMD should be developed, implemented, and evaluated.